2014
DOI: 10.1155/2014/218383
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Huoxiang Zhengqi Oral Liquid on Intestinal Mucosal Mechanical Barrier of Rats with Postinfectious Irritable Bowel Syndrome Induced by Acetic Acid

Abstract: In this study, a rat model with acetic acid-induced PI-IBS was used to study the role of HXZQ oral liquid in repairing the colonic epithelial barrier and reducing intestinal permeability. Pathomorphism of colonic tissue, epithelial ultrastructure, DAO activity in serum, and the protein expression of ZO-1 and occludin were examined to investigate protective effect mechanisms of HXZQ on intestinal mucosa barrier and then present experimental support for its use for prevention and cure of PI-IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…The immunohistochemistry study was performed as described previously ( 16 ). The mouse tissue sections (4 µm thick) were immersed in PBS and placed in polycarbonate staining jars (Kartell) filled with 10 mM sodium citrate buffer solution (pH 6.0).…”
Section: Methodsmentioning
confidence: 99%
“…The immunohistochemistry study was performed as described previously ( 16 ). The mouse tissue sections (4 µm thick) were immersed in PBS and placed in polycarbonate staining jars (Kartell) filled with 10 mM sodium citrate buffer solution (pH 6.0).…”
Section: Methodsmentioning
confidence: 99%
“…A rat model of the postinfectious irritable bowel syndrome induced by acetic acid was performed by reference of Liu et al [13] with slight modifications. Abdominal massage was performed according to our previous method [14].…”
Section: Reagents and Animalsmentioning
confidence: 99%
“…As a thousand-year-old formula, AL combines each component biological and pharmacological property and is an efficiency and low toxicity natural medicines. It is reported that the AL can increase the number of Lactobacillus, Bifidobacterial in mammal gut, reduce intestinal permeability in acetic acid-induced PI-IBS, regulate CD4+ and CD8+ cells in Peyer’s patch and suppress TNF-alpha levels in enteric homogenates to improve the diarrhea caused by Salmonella typhimurium in mice [9, 10, 36, 37, 38]. Our experiment found AL can effectively minimize the H9N2 AIV infection-induced intestinal mucosal injuries and alleviate bacterial flora disorder, suggesting that AL no only might somehow improve the immunity and anti-H9N2 AIV capabilities of host, but also repair intestinal barrier to prevent secondary infections.…”
Section: Discussionmentioning
confidence: 99%
“…Ageratum-Liquid (alcohol free) was used as a commercialized manufacture of Chinese herb medicine purchased from Taiji Group Chongqing Fuling Pharmaceutical Co., Ltd. (LOT number: 17021045, Approval Code: Z50020409, Chongqing, China) and used for treatment of the infection according the manufacturer’s instructions. Ageratum-Liquid is a Chinese patent medicine composed of 10 kinds of Chinese medical medicines, including Atractylodis Rhizoma, Citri Reticulatae Pericarpium, Magnoliae Ofcinalis Cortex, and Pinelliae Rhizoma, Angelicae Dahuricae Radix, Poria, and Arecae Pericarpium, Licorice extract, Patchouli oil and volatile oil in Perillae Folium, and the herbal prescription and reference compounds were relatively constant as previous description [10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation